Critical Role for the NLRP3 Inflammasome in Mediating IL-1β Production in Shigella sonnei-Infected Macrophages - Li, Lan-Hui; Chen, Tzu-Ling; Chiu, Hsiao-Wen; Hsu, Chung-Hua; Wang, Chien-Chun; Tai, Tzu-Ting; Ju, Tz-Chuen; Chen, Fang-Hsin; Chernikov, Oleg V.; Tsai, Wen-Chiuan; Hua, Kuo-Feng (Frontiers in Immunology, 2020)
Shigella is one of the leading bacterial causes of diarrhoea worldwide, affecting more than 165 million people annually. Among the serotypes of Shigella, Shigella sonnei is physiologically unique and endemic in human immunodeficiency virus-infected men who have sex with men. The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome, a protein complex composed of NLRP3, apoptosis-associated speck-like protein and caspase-1, recognizes and responds to pathogen infection and diverse sterile host-derived or environmental danger signals to induce IL-1β and IL-18 production. Although the Shigella flexneri-mediated activation of the NLRP3 inflammasome has been reported, the effect of S. sonnei on NLRP3 inflammasome activation remains unclear. We found that S. sonnei induced IL-1β production through NLRP3-dependent pathways in lipopolysaccharide-primed macrophages. A mechanistic study revealed that S. sonnei induced IL-1β production through P2X7 receptor-mediated potassium efflux, reactive oxygen species generation, lysosomal acidification and mitochondrial damage. In addition, the phagocytosis of viable S. sonnei was important for IL-1β production. Furthermore, we demonstrated that NLRP3 negatively regulated phagocytosis and the bactericidal activity of macrophages against S. sonnei. These findings provide mechanistic insight into the activation of the NLRP3 inflammasome by S. sonnei in macrophages.